Prevalensi Hasil Pemeriksaan HBsAg dan Anti HBs pada PSK (Pekerja Seks Komersial) - Priyatno, Djoko; Qomariyah, Nurul (Jaringan Laboratorium Medis, 2019)
Commercial sex workers are a high risk group of STD infection (HIV-AIDS, syphilis, gonorrhea and Hepatitis-B). Transmission of HBV 100x faster than the HIV. Diagnosis HBsAg and Anti-HBs is a marker of HBV infection can be detected at least 2 weeks before clinical symptoms appear. The incidence of STIs Semarang (in 2012) is the highest in the resocialization Argorejo as much as 1,623 cases. Monitoring of Hepatitis B in resocialization has not become a routine examination. The formulation of the research problem is "How prevalence of HBsAg and Anti-HBs on resocialization PSK Argorejo Semarang?". This study is observational analytic cross-sectional design. Specimens research is venous blood PSK Argorejo resocialization who check monitoring of HIV-AIDS in August-September 2015. Â Sampling a total of sampling for examination imunoserologis HBsAg and Anti-HBs in the strip method. Analysis of the relationship between host factors with HBsAg and anti-HBs using Spearman's test. Negative values on the results of HBsAg while the percentage of anti-HBs PSK resocialization some 29%. There is no relationship between age, education and knowledge with Anti-HBs. There is a relationship between sexual behavior with Anti-HBs. Upregulation required screening and immunization of Hepatitis-B infection in the community resocialization Argorejo Semarang.